Trends in the use of complementary and alternative medicine between 1987 and 2021 in Denmark - Sofie Rossen Møller; Ola Ekholm; Anne Illemann Christensen (BMC, 2024)
Abstract Background Complementary and alternative medicine (CAM) has been widely and increasingly used worldwide during the past decades. Nevertheless, studies in long-term trends of CAM use are limited. The aim of this study was to assess long-term trends in the prevalence of CAM use (both overall and for specific CAMs) between 1987 and 2021 in the adult Danish population and to examine certain sociodemographic characteristics of CAM users. Methods Data derived from nationally representative health surveys in the general adult population (≥ 16 years) in Denmark (the Danish Health and Morbidity Surveys) conducted in 1987, 1994, 2000, 2005, 2010, 2013, 2017, and 2021. The response proportion declined from 79.9% in 1987 to 45.4% in 2021. CAM use was assessed by questions on ever use of specific types of CAMs and overall use within the past 12 months. Differences in use of CAMs across educational levels were assessed using the Slope Index of Inequality (SII). Results An overall increase in the prevalence of CAM use within the past 12 months was found between 1987 (10.0%) and 2021 (24.0%). However, a stagnation was observed between 2010 and 2017, after which the prevalence decreased in 2021. In all survey waves, the prevalence was higher among women than men. For both sexes, the prevalence tended to be highest among respondents aged 25-44 years and 45-64 years. The group with 13-14 years of education had the highest prevalence of CAM use compared to the other educational groups (< 10 years, 10-12 years, and ≥ 15 years). SII values for both men and women increased between 1987 and 2021, which indicates an increase in differences of CAM use across educational groups. In all survey waves the most frequently used CAMs included massage and other manipulative therapies, acupuncture, and reflexology. Conclusions The use of CAM has increased markedly within the last decades and recently stagnated at high levels, which underlines the importance of securing high quality information and education for the public, health professionals, and legislators to ensure and promote safe use of CAMs.